IDENTIFICATION OF TYPES AND ABUNDANCE OF MICROPLASTICS IN BEACH SEDIMENTS IN PADANG CITY, WEST SUMATRA - Fitri, Sabrina Nur; Amin, Bintal; Yoswaty, Dessy (Asian Journal of Aquatic Sciences, 2024)
The presence of plastic waste in the ocean significantly impacts pollution. Lightweight plastic is transported by currents and waves, eventually accumulating in sediment. Its slow decomposition is influenced by composition and environmental conditions. Using a survey method at three stations in Padang City’s coastal waters, this study aims to investigate the composition and quantity of microplastics in sediment. Variations in microplastic levels across stations were analyzed using One-Way ANOVA, and differences between dry and wet zones and depths of 0-10 cm and 10-20 cm were examined with Independent Samples T-tests. Three microplastic categories were identified: fibers, fragments, and films, with an average concentration of 100.55 particles/kg. The Ulak Karang Beach estuary exhibited the highest particle concentration (129.16 particles/kg), whereas Banana Beach, characterized by minimal human activity, displayed the lowest concentration. There were significant differences (p<0.05) in the abundance of microplastics between stations. It was observed that the dry zone exhibited a higher concentration of particles (125.00 particles/kg) in contrast to the wet zone (76.66 particles/kg). In the 0-10 cm depth range, there was a higher abundance of microplastics (111.66 particles/kg) compared to the 10-20 cm depth range (89.44 particles/kg). The abundance of microplastics was significantly different (p<0.05) between the two coastal zones but not significantly different (p>0.05) between depths. Several possible causes of these differences were examined, but further research is needed to investigate other oceanographic factors and gain a more comprehensive understanding.